sol for exam 2 take home

# Hence the series in 5a and the series in 5c which can

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ∞ (5c) −1 m=2 ∞ ζm −1 m m−1 ∞ Solution for (5a) and (5c) : m=2 . Recall the result of (2a): ∞ −f x + g x (5d) , , ζm −1 m · 2m m=2 ζm −1 m · 2m m−1 ζm −1 m (5b) , = −1 m=2 ζm −1 m m−1 · xm . Hence the series in (5a), and the series in (5c), which can be rewritten as ∞ m=2 −1 ∞ m=2 −1 m−1 ζm −1 m m−1 ζm −1 m · 1m , 1 2 · and m , respectively, are nothing else but −f 1 + g 1 , and respectively. Accordingly, substitute −f x + g x and obtain 1 − γ − ln 2, = and 1 2 −f x=1 1−γ 1−γ 2 13 and x− − ln +g 1 2 x= 1 2 , into ln Γ 2 + x 3√ π, 4 respectively. Solution for (5b) and (5d) : Recall the result of (2b): ∞ f x +g x = m=2 ζm −1 m · xm . Hence the series in (5b), and the series in (5d), which can be rewritten as ∞ ζm −1 m ζm −1 m m=2 · 1m , · 1 2 f 1 2 ∞ m=2 and m , respectively, are nothing else but f 1 +g 1, and x=1 respectively. Accordingly, substitute f x +g x and obtain 1 − γ, and = 1−γ 1−γ 2 x+ + ln 14 1 2 +g and x= , 1 2 into ln Γ 2 − x 1√ π, 2 respectively. Answers for (5a), (5b), (5c) and (5d) : ∞ (5a) m=2 ∞ (5b) m=2 −1 m=2 ∞ (5d) m=2 ζm −1 m ζm −1 m ∞ (5c) m−1 −1 m−1 = 1 − γ − ln 2, = 1 − γ, ζm −1 m · 2m 15 1−γ 2 − ln 3√ π, 4 = ζm −1 m · 2m = 1−γ 2 + ln 1√ π. 2...
View Full Document

## This note was uploaded on 01/12/2014 for the course MATH 116 taught by Professor Scholle,minho during the Fall '08 term at Kansas.

Ask a homework question - tutors are online